2020
DOI: 10.1080/19475683.2020.1831603
|View full text |Cite
|
Sign up to set email alerts
|

Airbnb and crime in Barcelona (Spain): testing the relationship using a geographically weighted regression

Abstract: The existence of works proving the possible relationship empirically that Airbnb lodgings could have with crime in Spain is not known. This research analyzes the relationship between Airbnb lodgings and crimes against the properties and people in Barcelona's neighbourhoods. To achieve this, we use an ordinary least squares regression model and a geographically weighted regression model. The results show a significant and positive relationship between the higher density of Airbnb lodgings and the higher crime r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…We found that the presence of international visitors is a consistent explanatory variable of the likelihood of residents becoming victims of robbery, especially outside work-days (i.e., at weekends, in the summer, and on Christmas holidays). The models also depict a connection between the presence of tourists and the residential instability of the host neighbourhoods, which goes in the same direction as previous analyses of the negative externalities of tourism in Barcelona (Cocola-Gant & López-Gay, 2020 ; Garcia-López et al, 2020 ; Maldonado-Guzmán, 2020 ). The sustained and massive influx of visitors is changing the social composition of neighbourhoods in Barcelona.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We found that the presence of international visitors is a consistent explanatory variable of the likelihood of residents becoming victims of robbery, especially outside work-days (i.e., at weekends, in the summer, and on Christmas holidays). The models also depict a connection between the presence of tourists and the residential instability of the host neighbourhoods, which goes in the same direction as previous analyses of the negative externalities of tourism in Barcelona (Cocola-Gant & López-Gay, 2020 ; Garcia-López et al, 2020 ; Maldonado-Guzmán, 2020 ). The sustained and massive influx of visitors is changing the social composition of neighbourhoods in Barcelona.…”
Section: Discussionsupporting
confidence: 76%
“…Arias-Sans and Russo ( 2016 ) focused on the creation of tourism-only areas in the city, areas that are no longer publicly accessible, such as Park Güell. The effect of tourism on crime has also been addressed by Maldonado-Guzmán ( 2020 ), who highlights the significant relationship between Airbnb lodgings and property crime in Barcelona.…”
Section: The Case Study: Barcelona a Densely Populated City With An E...mentioning
confidence: 97%
“…This transnational gentrification has also caused extremely low ratios of local population in some neighbourhoods, as in the Raval and Gòtic. Such dynamics can play key roles in crime levels, as Maldonado-Guzmán (2020) suggested by analyzing the density of Airbnb lodgings positively associated with higher crime rates, especially property crime.…”
Section: Discussionmentioning
confidence: 99%
“…When development projects are unevenly distributed, the decision to commit a crime may be motivated. Residents who may not benefit directly or indirectly from the allocation of development projects will find it beneficial to move to the beneficiary areas to compete with the local people for the positive externalities of these projects (Maldonado-Guzmán, 2020;Xu et al, 2017). However, if they are not successful in competing for these interests, the next option may be to attack the beneficiaries.…”
Section: Related Literaturementioning
confidence: 99%